Meta‐cognitive skills training enhances computerized cognitive remediation outcomes among individuals with first‐episode psychosis. Issue 3 (15th October 2015) - Breitborde, Nicholas J.K.; Woolverton, Cindy; Dawson, Spencer C.; Bismark, Andrew; Bell, Emily K.; Bathgate, Christina J.; Norman, Kaila
Abstract: Aim: Meta‐cognitive skills training (MST) is a frequent component of cognitive remediation programmes for individuals with psychosis. However, no study has investigated whether incorporating such activities produces increased clinical benefits compared with computerized cognitive remediation alone. Methods: Individuals with first‐episode psychosis who completed computerized cognitive remediation with concurrent meta‐cognitive skills training (CCR + MST) were compared with a historical control group who received computerized cognitive remediation alone (CCR) and did not differ from the CCR + MST group with regard to pre‐intervention cognition, diagnosis, age, duration of psychotic illness or sex. Participants completed assessments of cognition and real‐world functioning before and after 6 months of treatment. Results: Individual receiving CCR + MST experience greater gains in cognition and real‐world functioning than individuals who received CCR. Conclusions: MST may be an important component within cognitive remediation programmes for first‐episode psychosis.